HLA-associated polymorphisms in the HIV-2 capsid highlight key differences between HIV-1 and HIV-2 immune adaptation. (27th March 2018) - de Silva, Thushan I.; Leligdowicz, Aleksandra; Carlson, Jonathan; Garcia-Knight, Miguel; Onyango, Clayton; Miller, Nicholas; Yindom, Louis-Marie; Hué, Stephane; Jaye, Assan; Dong, Tao; Cotten, Matthew; Rowland-Jones, Sarah L.
Abstract : Objective: HIV-1 frequently adapts in response to immune pressure from cytotoxic T-lymphocytes (CTL). Many HIV-2 infected individuals have robust capsid-specific CTL responses associated with viral control. Despite this CTL pressure, adaptive changes in this key immunogenic HIV-2 protein have not previously been described. We sought to compare selective pressure on HIV-1 and HIV-2 capsids and identify HLA-associated viral polymorphisms in HIV-2. Design and methods: Bioinformatic algorithms to identify sites under positive and negative selective pressure and a statistical model of evolution to identify HLA- associated polymorphisms in HIV-2 was applied to sequences from a community cohort in Guinea-Bissau. IFN-γ ELISpots were used to compare T-cell responses to wild-type and variant epitopes. Results: We identified greater purifying selection and less sites under positive selective pressure in HIV-2 compared with HIV-1. Five HIV-2 codons with HLA- associated polymorphisms were detected all within or around known or predicted CTL epitopes. One site was within the HLA -B58 SuperType (ST)-restricted epitope (TSTVEEQIQW), the HIV-2 equivalent of the HIV-1 TW10 epitope. In contrast to HIV-1, where a T→N mutation at position 3 is associated with resulting loss of CTL control, an E→D mutation at position 5 was observed in HIV-2. Robust CTL responses to the variant HIV-2 epitope were seen, suggesting that HIV-2 adaptation may be at the level of T-cell receptor recognition. Conclusion: Greater constraints on evolution may exist in HIV-2, resulting in more purifying selection and different immune adaptation pathways in HIV-1 and HIV-2 capsids. This may allow CTL responses to persist in HIV-2. Abstract : Supplemental Digital Content is available in the text